СӨЗ ОЙЫН ҚОСЫҚЛАРЫ – ҚАРАҚАЛПАҚ БАЛАЛАР ФОЛЬКЛОРЫНЫҢ ӨЗ АЛДЫНА БИР ЖАНРЫ СЫПАТЫНДА - Бийсенбаев, Қ. (SCIENCE and SOCIETY, 2022)
The article discusses the peculiarities, history, lyrical and dramatic features of the genre of "Word game songs" belonging to the Karakalpak folklore, including children’s folklore. This genre is also analyzed as an independent genre of folk art.